(untitled) (International Journal of Engineering and Computer Science, 2018)
Image enhancement is a necessary step in image processing. The primary goal of image processing is to achieve better visualization so that they could more efficient for human beings and machines. This paper provides description of image using spatial domain and frequency domain.